Gut microbiome features associate with immune checkpoint inhibitor response in individuals with non-melanoma skin cancers: an exploratory study - Yujie Zhao; Jacqueline T. Ferri; James R. White; Megan D. Schollenberger; Kim Peloza; Cynthia L. Sears; Evan J. Lipson; Fyza Y. Shaikh (Microbiology Spectrum)
ABSTRACT Immune checkpoint inhibitor (ICI) therapy has yielded revolutionary outcomes among some individuals with skin cancer, but a large percentage of individuals do not benefit from these treatments. The gut microbiota is hypothesized to impact ICI therapy outcomes. However, data on ICI therapy, gut microbiota, and non-melanoma skin cancers are limited. To examine the association of gut microbiota structure and function with non-melanoma skin cancer ICI outcomes, we performed 16S rRNA V1-V2 gene amplicon sequencing of 68 fecal samples collected longitudinally from individuals with basal cell carcinoma (n = 5), Merkel cell carcinoma (n = 5), or cutaneous squamous cell carcinoma (CSCC, n = 11), followed by tumor-dependent differential analyses of bacterial composition and fecal sample analysis by untargeted metabolomics. Across all tumor types, we identified 10 differential bacterial genera between responders (R) or non-responders (NR) to ICI therapy. Among individuals with CSCC, we identified 10 genera and 20 species that differentiated between R and NR and yielded 8 pathways enriched in NR and 12 pathways enriched in R by predicted functional pathway analyses. Untargeted fecal metabolomics to examine putative gut microbiota metabolites associated with CSCC ICI R/NR identified nine KEGG pathways associated with ICI efficacy. In summary, this exploratory study suggests gut microbiota features that are associated with ICI efficacy in individuals with non-melanoma skin cancers and highlights the need for larger studies to validate the results.IMPORTANCEPrior studies examining associations between ICI efficacy and the gut microbiome have focused primarily on individuals with melanoma, for whom ICI therapy was first approved. Meanwhile, data regarding microbiome features associated with ICI responses in individuals with non-melanoma skin cancers (NMSCs) have remained limited. This initial fecal microbiota examination of individuals with NMSCs suggests that larger-scale studies to extend and validate our findings may yield predictive or prognostic biomarkers for individuals with NMSC receiving ICI with potential to provide insight to complementary, effective therapeutic interventions through microbiota modification.